1988
DOI: 10.1080/00103628809367953
|View full text |Cite
|
Sign up to set email alerts
|

Automated instrumental analysis of carbon and nitrogen in plant and soil samples

Abstract: An automated CHN Analyzer was compared with the Walkley-Black and Kjeldahl methods for organic carbon (C) and nitrogen (N). Four organic compounds, twenty nine plant materials and five soils were tested. The CHN Analyzer gave C and N values that were not significantly different (P<0.05) to the theoretical weight percents of the organic compounds. The Walkley Black method gave soil C values significantly lower (P<0.05) than those obtained with the CHN Analyzer. The Kjeldahl method gave soil N values significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
112
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(113 citation statements)
references
References 4 publications
1
112
0
Order By: Relevance
“…In most of the samples, C concentration determined through Walkley-Black method was lower than that obtained through dry combustion (Figure 1), possibly because of incomplete oxidation of the total organic C in the Walkley-Black procedure (McGeehan & Naylor, 1988;Nelson & Sommers, 1996). By taking the inverse of the linear regression in Figure 1d, a correction equation is thus proposed to be applied on the C concentration results of Walkley-Black: C = 1.05C W.Black + 0.47.…”
Section: Comparison Of Methods For C Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…In most of the samples, C concentration determined through Walkley-Black method was lower than that obtained through dry combustion (Figure 1), possibly because of incomplete oxidation of the total organic C in the Walkley-Black procedure (McGeehan & Naylor, 1988;Nelson & Sommers, 1996). By taking the inverse of the linear regression in Figure 1d, a correction equation is thus proposed to be applied on the C concentration results of Walkley-Black: C = 1.05C W.Black + 0.47.…”
Section: Comparison Of Methods For C Determinationmentioning
confidence: 99%
“…Therefore, no correction was necessary for the Kjeldahl-N results. The tendency, however, for the higher concentrations obtained by dry combustion could be related to a non quantitatively release of some refractory N, or of N in N-O structures of NO 3 - (McGeehan & Naylor, 1988;Bremner, 1965).…”
Section: Comparison Of Methods For N Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tubers were diced into small pieces and freeze-dried. Once dried, tuber pieces were ground to a fine powder, weighed, and analyzed for percent nitrogen, dry weight, by using a LECO combustion analyzer CNS-2000 (LECO, St. Joseph, MI) (16), at the Analytical Sciences Laboratory, University of Idaho Holm Research Center, Moscow, ID.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies found proportional but slightly lower (McGeehan and Naylor 1988;Vittori Antisari and Sequi 1988) or higher (Kowalenko 2001) soil total N values for the Kjeldahl method compared with the dry combustion method. High concentrations of nitrate (NO 3 )-N in soil samples, and lack of pretreatment for including NO 3 -N in the Kjeldahl method, could contribute to lower measured total N concentrations by the Kjeldahl method compared with the combustion method (Rutherford et al 2007).…”
Section: Introductionmentioning
confidence: 99%